Analisis Pengaruh Store Atmosphere, Harga Dan Lokasi Terhadap Minat Beli Konsumen Di Toko Buku Togamas Solo - Ayu Anjani, Dini, Basworo Dibyo, S.E, M.Si (2015)
This study aims to determine the effect of store atmosphere, price and location, either partially or simultaneously on consumer buying interest Togamas Solo bookstore. Lists different types of research survey with questionnaires uses as an instrument. The sample used was consumer bookstore Solo Togamas totaling 100 people using purposive sampling. The analytical method used was Validity Test, Reliability Test, Test Normality, Multicollinearity Test, Test Heteroskidastity, Multiple Linear Regression Analysis, t test, F test, and test R². These results indicate that multiple linear regression significant and positive impact on consumer buying interest in the bookstore Togamas Solo variable store atmosphere, price and location. Moreover, from the F test resulted F_hitung greater than F_tabel so that Ho is rejected, it means the independent variable (store atmosphere, price and location) significantly influence consumer purchase interest in a book store Togamas Solo. R² calculation value of 0.358. Value shows together three independent variables have an influence on the dependent variable amounted to 35.8% and the remaining 64.2% is influenced by other variables not examined in this study.